Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the rational equation [tex]\(\frac{x-10}{x} = \frac{99}{x+10}\)[/tex], we need to find the values of [tex]\(x\)[/tex] that satisfy this equation. Here is the step-by-step solution:
1. Combine the fractions and simplify:
[tex]\[ \frac{x-10}{x} = \frac{99}{x+10} \][/tex]
To eliminate the fractions, we cross-multiply:
[tex]\[ (x-10)(x+10) = 99x \][/tex]
2. Expand both sides:
[tex]\[ x^2 - 100 = 99x \][/tex]
3. Rearrange the equation:
[tex]\[ x^2 - 99x - 100 = 0 \][/tex]
4. Solve the quadratic equation [tex]\(x^2 - 99x - 100 = 0\)[/tex] using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -99\)[/tex], and [tex]\(c = -100\)[/tex]:
- Compute the discriminant:
[tex]\[ b^2 - 4ac = (-99)^2 - 4(1)(-100) = 9801 + 400 = 10201 \][/tex]
- Take the square root of the discriminant:
[tex]\[ \sqrt{10201} = 101 \][/tex]
- Apply the quadratic formula:
[tex]\[ x = \frac{-(-99) \pm 101}{2(1)} = \frac{99 \pm 101}{2} \][/tex]
5. Calculate the solutions:
- For the positive root:
[tex]\[ x = \frac{99 + 101}{2} = \frac{200}{2} = 100 \][/tex]
- For the negative root:
[tex]\[ x = \frac{99 - 101}{2} = \frac{-2}{2} = -1 \][/tex]
Therefore, the solutions to the equation [tex]\(\frac{x-10}{x} = \frac{99}{x+10}\)[/tex] are:
[tex]\[ x = [-1, 100] \][/tex]
1. Combine the fractions and simplify:
[tex]\[ \frac{x-10}{x} = \frac{99}{x+10} \][/tex]
To eliminate the fractions, we cross-multiply:
[tex]\[ (x-10)(x+10) = 99x \][/tex]
2. Expand both sides:
[tex]\[ x^2 - 100 = 99x \][/tex]
3. Rearrange the equation:
[tex]\[ x^2 - 99x - 100 = 0 \][/tex]
4. Solve the quadratic equation [tex]\(x^2 - 99x - 100 = 0\)[/tex] using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -99\)[/tex], and [tex]\(c = -100\)[/tex]:
- Compute the discriminant:
[tex]\[ b^2 - 4ac = (-99)^2 - 4(1)(-100) = 9801 + 400 = 10201 \][/tex]
- Take the square root of the discriminant:
[tex]\[ \sqrt{10201} = 101 \][/tex]
- Apply the quadratic formula:
[tex]\[ x = \frac{-(-99) \pm 101}{2(1)} = \frac{99 \pm 101}{2} \][/tex]
5. Calculate the solutions:
- For the positive root:
[tex]\[ x = \frac{99 + 101}{2} = \frac{200}{2} = 100 \][/tex]
- For the negative root:
[tex]\[ x = \frac{99 - 101}{2} = \frac{-2}{2} = -1 \][/tex]
Therefore, the solutions to the equation [tex]\(\frac{x-10}{x} = \frac{99}{x+10}\)[/tex] are:
[tex]\[ x = [-1, 100] \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.